Cardiovascular and all-cause mortality in patients with intermittent claudication and critical limb ischaemia. Issue 3 (8th November 2017) - van Haelst, S T W; Koopman, C; den Ruijter, H M; Moll, F L; Visseren, F L; Vaartjes, I; de Borst, G J
Abstract: Background: The aim of this study was to evaluate absolute mortality risks and to determine whether changes in mortality risk occurred in patients with intermittent claudication (IC) or critical limb ischaemia (CLI) in the Netherlands between 1998 and 2010. Methods: Data for patients treated between 1998 and 2010 were obtained from Dutch nationwide registers: the Hospital Discharge Register, Population Register and Cause of Death Register. The registers were used to obtain information regarding IC and CLI hospitalizations, co-morbidities, demographic factors, and date and cause of death. The cohort was split into two time intervals for comparison: 1998–2004 (period 1) and 2005–2010 (period 2). Thirty-day mortality was excluded to eliminate per-admission complications. One- and 5-year cardiovascular and all-cause mortality rates were compared with those of a representative sample of the general Dutch population (28 494 persons) by Cox proportional hazards models. Results: Some 47 548 patients were included, 34 078 with IC and 13 470 with CLI. In patients with IC, the age-adjusted 5-year mortality risk for cardiovascular disease decreased significantly in period 2 (14·1 per cent) compared with that in period 1 (16·1 per cent) in men only (5-year adjusted hazard ratio (HR) 0·76, 95 per cent c.i. 0·69 to 0·83; P < 0·001). In patients with CLI, the cardiovascular mortality risk decreased significantly only in women, with the 5-year risk reducing from 31·2 per cent in period 1 to 29·2 per cent in period 2 (adjusted HR 0·84, 0·74 to 0·94; P = 0·004). Compared with the general population, the mortality risk in patients with IC was increased between 1·70 (1·58 to 1·83) and 3·20 (2·69 to 3·81) times, and in those with CLI the risk was increased between 2·24 (2·09 to 2·40) and 5·19 (4·30 to 6·26) times. Conclusion: The risk of premature death in patients with IC and CLI declined significantly in the Netherlands, in a sex-specific manner, over the period from 1998 to 2010. The absolute risk of cardiovascular mortality remains high in these patients. Abstract : Declining mortality; large burden of cardiovascular deaths